Acute-phase clinical profile and quality of life in patients with chikungunya during the 2025 outbreak in Bangladesh: A facility-based cross-sectional study - Mohammad Jahid Hasan; Md. Shahabul Huda Chowdhury; Muna Islam; Sadia Islam; Tanzin Naher; H.M. Hamidullah Mehedi; Abu Saif Mohammad Lutful Kabir; Jannatul Fardous; Refaya Tasnim; Asif Ahmed; Md. Atiquel Islam Chowdhury; Madhabi Karmaker; et al. (PLOS Neglected Tropical Diseases, 2026)
Background Bangladesh experienced a notable resurgence of chikungunya cases in 2025, following its last major outbreak in 2017. This study aimed to characterize the epidemiological profile of laboratory-confirmed chikungunya cases in Bangladesh. Methods This cross-sectional study included and interviewed 442 laboratory-confirmed adult chikungunya cases. Pain was assessed using the Visual Analog Scale (VAS, 0–10) and quality of life was measured via the validated Bangla EQ-5D-3 L instrument, which evaluates five domains—mobility, self-care, usual activities, pain/discomfort, and anxiety/depression. Overall health was rated using the EQ-VAS, a vertical scale ranging from 0 (“worst imaginable health state”) to 100 (“best imaginable health state”). Index scores were derived using the trade-off (TTO) valuation set. Associations with the overall EQ-5D index were analyzed using Tobit regression, whereas domain-specific associations were examined via ordinal logistic regression models. Results Of all, 16.5% of patients required hospital admission, with a median length of stay of 5 days (IQR 3–6), and the rest of them consulted on an outdoor basis. The mean (SD) age of the participants was 45·3 (15·5) years, and 60% were female. Fever (98%) and arthralgia (97%) were the predominant symptoms. Mild pain was reported by 6% of patients, while 40% had moderate and 54% had severe pain, with a median VAS score of 8.0 (IQR 7.0–9.0). Over 70% of the participants reported mobility limitations, self-care, functional impairment, pain or psychological symptoms. The median EQ-5D index was 0·78 (IQR 0·60-0·96). Female sex (β = –0·10, 95% CI –0·17, –0·02) and greater pain severity (β = –0·26, 95% CI –0·37, –0·15) were independently associated with a lower EQ-5D index. Conclusions During the outbreak, chikungunya patients in Bangladesh predominantly presented with fever and joint pain and experienced marked declines in quality of life, with women being disproportionately affected.